HMGA1 induces EZH2 overexpression in human B-cell lymphomas - De Martino, Marco (Am J Cancer Res, 2021)
EZH2 is an enzymatic subunit of PRC2, an epigenetic regulator that triggers the methylation of the histone H3 lysine 27 silencing the transcription of several genes. EZH2 has a critical role in cancer progression, since its overexpression has been associated with increased cancer cell invasiveness, drug resistance and poor patient survival. However, the mechanisms accounting for EZH2 overexpression in cancer remain still unclear. Intriguingly, also HMGA protein overexpression is a feature of many human malignancies and correlates with the presence of metastases and a poor outcome. The HMGA proteins, including HMGA1 and HMGA2, belong to the architectural transcription factors that play a key role in the organization of chromatin structure. Here, we report a statistically significant correlation between HMGA1 and EZH2 expression in human lymphomas. We demonstrate that HMGA1 is able to bind EZH2 promoter and induce its activity. Consistently, silencing of HMGA1 expression results in the downregulation of the EZH2 levels leading to a decreased proliferation and migration rate of human lymphoma cell lines. Therefore, these data identify HMGA1 as an EZH2 activator, suggesting a novel molecular mechanism contributing to EZH2 overexpression in human malignancies and a synergism of these proteins in cancer progression.